Defective Bone Microstructure in Hydronephrotic Mice: A Histomorphometric Study in ICR/Mlac‐hydro Mice. Issue 2 (14th November 2013) - Suntornsaratoon, Panan; Wongdee, Kannikar; Tiyasatkulkovit, Wacharaporn; Ampawong, Sumate; Krishnamra, Nateetip; Kengkoom, Kanchana; Charoenphandhu, Narattaphol
ABSTRACT Chronic renal impairment can lead to bone deterioration and abnormal bone morphology, but whether hydronephrosis is associated with bone loss remains unclear. Herein, we aimed to use computer‐assisted bone histomorphometric technique to investigate microstructural bone changes in Imprinting Control Region (ICR) mice with a spontaneous mutation that was associated with bilateral nonobstructive hydronephrosis (ICR/Mlac‐hydro). The results showed that 8‐week‐old ICR/Mlac‐hydro mice manifested decreases in trabecular bone number and thickness, and an increased trabecular separation, thereby leading to a reduction in trabecular bone volume compared with the wild‐type mice. Furthermore, histomorphometric parameters related to both bone resorption and formation, that is, eroded surface, osteoclast surface, and osteoblast surface, were much lower in ICR/Mlac‐hydro mice than in the wild type. A decrease in moment of inertia was found in ICR/Mlac‐hydro mice, indicating a decrease in bone strength. In conclusion, ICR/Mlac‐hydro mice exhibited trabecular bone loss, presumably caused by marked decreases in both osteoblast and osteoclast activities, which together reflected abnormally low bone turnover. Thus, this mouse strain appeared to be a valuable model for studying the hydronephrosis‐associated bone disease. Anat Rec, 297:208–214, 2014. © 2013 Wiley Periodicals, Inc.